Quality of Favorite Places in Community Residents in The Islamic Village of Kepaon, Pemogan, Denpasar - Widyatma, Gede Herry (Journal of A Sustainable Global South; Vol 5 No 1 (2021): February 2021, 2021)
The existence of a favorite place is a public space that has an important role in the development of villages in urban areas. In the city of Denpasar there are many kampung-kampung (kampung-kampung: a community) that have many favorite places, where the existence of favorite places itself has quality with various facilities. This study aims to determine the quality of people's favorite places in the neighborhood. This study aims to determine the quality of people's favorite places in their neighborhood. The focus of the problem raised is places that are considered favorite by the people in their neighborhood and how the quality of physical object facilities, non-physical object facilities and infrastructure facilities at the favorite places. The research method used is a qualitative method, with a case study approach, the technique for collecting research data is through interview techniques, where the speakers come from people who live in Kepaon Islamic Kampung, Pemogan, Denpasar, asked to write on a piece of paper the places that people consider favorite according to their feelings, this writing technique aims to avoid the occurrence of the expression of feelings towards a favorite place between one resource person with another resource person. This research shows that there are many favorite places in the area of Kampung Islam, Kepaon, Pemogan, Denpasar, but favorite places that have quality with good facilities that are chosen by many people in their neighborhoods such as; Al-Muhajirin Kepaon Mosque, Sungai Taman Pancing Tukad Badung, Kertha Boga Market. The role of the community as well as the government is able to care for and maintain the quality of these favorite places, so that the community is guyub (guyub: close-knit interaction) to live in the area.   Index Terms — favorite places, community, neighborhood